COVID-19 Related Experience, Knowledge, Attitude, and Behaviors Among 2,669 Orthodontists, Orthodontic Residents, and Nurses in China: A Cross-Sectional Survey - Hua, Fang; Qin, Danchen; Yan, Jiarong; Zhao, Tingting; He, Hong (Frontiers in Medicine, 2020)
Objectives: To assess the current COVID-19 related experience, knowledge, attitude and behaviors among orthodontists, orthodontic residents and orthodontic nurses in China, and to identify factors associated with their self-perceived and actual level of knowledge, as well as their willingness to treat/care for COVID-19 patients. Materials and Methods: A cross-sectional online survey was conducted in China, using a 37-item questionnaire developed based on previous research. A professional online survey tool (www.wjx.cn) and a social media platform (WeChat) were used to display and distribute the questionnaire. Data were collected during April 11 to 13, 2020, when most regions of China had resumed dental practice except for high-risk regions such as Wuhan. We then analyzed the collected data with multivariable generalized estimating equations. Results: A total of 2669 valid questionnaires were collected. Orthodontic services were suspended for nearly all respondents (97.8%) during the epidemic, and 68.0% had resumed work. The majority of respondents (80.2%) were confident that they understood COVID-19 related knowledge, but most of them only correctly answered less than half of the questions testing their actual level of knowledge. About two-thirds (64.1%) were willing to treat/care for patients with confirmed or suspected COVID-19. The completion of relevant training programs was significantly associated with more confidence in knowledge mastery (P < 0.001) and higher actual level of knowledge (P < 0.001), but did not increase their willingness to treat/care for patients with COVID-19 (P = 0.235). Conclusions: Before work resumption, COVID-19 related training programs are essential for the improvement of knowledge, confidence and preparedness of orthodontic professionals. Sufficient and proper protection should also be provided to ensure their safety and reduce their psychological burden. Clinical Relevance: The findings can provide evidence for policy-making related to the resumption of elective dental services.